Clinical relevance of pathological diagnosis of Hirschsprung's disease with acetylcholine-esterase histochemistry or calretinin immunohistochemistry - Romero, Philipp; Burger, Astrid; Wennberg, Erica; Mellein, Stefanie; Holland-Cunz, Stefan; Schwab, Constantin; Günther, Patrick (Children, 2024)
Introduction: Hirschsprung disease (HD) manifests as a developmental anomaly affecting the enteric nervous system, where there is an absence of ganglion cells in the lower part of the intestine. This deficiency leads to functional blockages within the intestines. HD is usually confirmed or ruled out through rectal biopsy. The identification of any ganglion cells through hematoxylin and eosin (H&E) staining rules out HD. If ganglion cells are absent, further staining with acetylcholine-esterase (AChE) histochemistry or calretinin immunohistochemistry (IHC) forms part of the standard procedure for determining a diagnosis of HD. In 2017, our Institute of Pathology at University Hospital of Heidelberg changed our HD diagnostic procedure from AChE histochemistry to calretinin IHC. In this paper, we report the impact of the diagnostic procedure change on surgical HD therapy procedures and on the clinical outcome of HD patients. Methods: We conducted a retrospective review of the diagnostic procedures, clinical data, and postoperative progress of 29 patients who underwent surgical treatment for HD in the Department of Pediatric Surgery, University of Heidelberg, between 2012 and 2021. The patient sample was divided into two groups, each covering a treatment period of 5 years. In 2012-2016, HD diagnosis was performed exclusively using AChE histochemistry (AChE group, n = 17). In 2017-2021, HD diagnosis was performed exclusively using calretinin IHC (CR group, n = 12). Results: There were no significant differences between the groups in sex distribution, weeks of gestation, birth weight, length of the aganglionic segment, or associated congenital anomalies. Almost half of the children in the AChE group, twice as many as in the CR group, required an enterostomy before transanal endorectal pull-through procedure (TERPT). In the AChE group, 4 patients (23.5%) required repeat bowel sampling to confirm the diagnosis. Compared to the AChE group, more children in the CR group suffered from constipation post TERPT. Discussion: Elevated AChE expression is linked to hypertrophied extrinsic cholinergic nerve fibers in the aganglionic segment in the majority of patients with HD. The manifestation of increased AChE expression develops over time. Therefore, in neonatal patients with HD, especially those in the first 3 weeks of life, an increase in AChE reaction is not detected. Calretinin IHC reliably identifies the presence or absence of ganglion cells and offers multiple benefits over AChE histochemistry. These include the ability to perform the test on paraffin-embedded tissue sections, a straightforward staining pattern, a clear binary interpretation (negative or positive), cost-effectiveness, and utility regardless of patient age. Conclusions: The ability of calretinin IHC to diagnose HD early and time-independently prevented repeated intestinal biopsies in our patient population and allowed us to perform a one-stage TERPT in the first months of life, reducing the number of enterostomies and restoring colonic continuity early. Patients undergoing transanal pull-through under the age of 3 months require a close follow-up to detect cases with bowel movement problems.